Effect of Alumina Nanofibers Content on the Microstructure and Properties of ATZ Composites Fabricated by Spark Plasma Sintering; Materials Today: Proceedings; Vol. 11, Pt. 1 : International Conference on Modern Trends in Manufacturing Technologies and Equipment 2018 - Leonov A. A. Andrey Andreevich (2019, 2019)
Title screen